Chest CT texture analysis for response assessment in systemic sclerosis. Issue 101 (April 2018) - Kloth, C.; Henes, J.; Xenitidis, T.; Thaiss, W.M.; Blum, A.C.; Fritz, J.; Nikolaou, K.; Horger, M.; Ioanoviciu, Sorin Dumitru
Highlights: CT-textural features after SCT correlate with those of visual CT-evaluation of lung abnormalities. CT-textural features provide information about therapy-induced structural pulmonary changes. CT-textural features predict potential reversibility of ILD and thus response to therapy. CT-textural analysis shows improvement even in the non-responders thus correlating with mRSS-tests-course. Abstract: Purpose: To evaluate the role of CT-textural features for monitoring lung involvement in subjects with systemic sclerosis(SSc) undergoing autologous stem cell transplantation(SCT) by comparison with semi-quantitative chest-CT, pulmonary function tests(PFT) and clinical parameters (modified Rodnan skin score[mRSS]). Methods: In a retrospective single centre analysis, we identified 23 consecutive subjects(11male) with SSc between 07/2005 and 11/2016 that underwent chest CTs before, 6 and 12 months post-SCT. Response to therapy was defined at 6 months after transplantation as stabilisation or improvement in FVC > 10% and DLCOSB > 10%. CT-texture analysis(CTTA) including mean, entropy and uniformity were calculated. Results: PFT classified the subjects into responders(18/23;78%) and non-responders(5/23;22%). mRSS improved in responders from 28.46 ± 9.53 to 15.70 ± 10.07 6 months after auto-SCT ( p = .001) whereas in non-responders no significant improvement was registered. Fibrosis score increased significantly(mean2.33 ± 1.23 vs.1.41 ± 0.78; p = .005) in non-responders after 6 and 12months. Significant lower mean intensity and entropy of skewness and higher uniformity of skewness was found in responders vs. non-responders at baseline. Significant changes in CTTA-parameters were found in both responders and non-responders at 6months and only in responders also at 12months post-SCT. Conclusions: Changes in CT-textural features after SCT are associated with visual CT evaluation of SSc-related lung abnormalities, but complementary provide information about therapy-induced, structural pulmonary changes.